Pengaruh Demografi dan Ekonomi Terhadap Pengeluaran Kesehatan Studi Kasus di ASEAN - Panogu, Mateus Arif; Sihaloho, Estro Dariatno (Universitas Negeri Padang, 2024)
The countries that are a part of the Association of Southeast Asian Nation (ASEAN) exhibit dynamic demographic and economic charateristics. This study aims to analyze the relationship between GDP per capita, the precentage of the population aged 65 and above, and the level of urbanization on healthcare expenditure in ASEAN countries, thereby providing deeper insights into healthcare spending in the ASEAN regions. Additionally, another objetive of this study is to identify the key factors influencing healthcare expenditure in ASEAN countries. The methodology employed in this study is panel data analysis, which includes three models: Pooled Ordinary Least Squares (POLS), Fixed Effect Model, and Random Effect Model. To determine the appropriate model for the study, statistical tests will be conducted. The statistical tests utilized in this study are the Chow Test and the Hausmant Test. The results indicates that the percentage of the population aged 65 and above, the level of urbanization, and GDP per capita have significant impacts on healthcare expenditure. Futhermore, the perentage of the population aged 65 and above has the most substantial impact compared to the level of urbanization and GDP per capita.